Analisis Ushul Fiqh dalam Karya Sastra Ronggeng Dukuh Paruk Karya Ahmad Tohari - Muhammad Rafif Athallah; Arvi Farand Arkani; Arin Nisa Rabbani; Mutiara Salsabila Nuzula; Tenny Sudjatnika (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes Ahmad Tohari’s novel Ronggeng Dukuh Paruk through the perspective of Usul Fiqh (Islamic jurisprudence) to reveal how customs that live in society can give rise to social practices that contradict the principles of sharia. Using descriptive-qualitative methods and content analysis techniques, this study examines six main concepts of Usul Fiqh, namely ’urf, maslahat-mafsadat, sadd dzarā’i, illat, dalālah, and maqāshid sharia. The results of the study indicate that the Dukuh Paruk custom is categorized as ’urf fasid because it is rooted in mystical beliefs and practices that degrade human dignity. The assessment of maslahat carried out by the community is pseudo and does not meet the criteria of maslahah sharia. The ronggeng tradition opens the door to mafsadat through body manipulation, the loss of private boundaries, and uncontrolled social interactions. The illat used by traditional figures is mostly invalid according to ushuliyyah, while Rasus appears as a figure who demonstrates more rational moral considerations. The analysis of dalālah reveals explicit and implicit messages regarding social decay, while the study of maqāshid confirms that the five basic objectives of sharia are not realized in the life of Dukuh Paruk. This research demonstrates that Usul Fiqh can be an effective analytical tool for evaluating cultural practices that deviate from Islamic values